2018
DOI: 10.1111/jam.13711
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol stress in Oenococcus oeni : transcriptional response and complex physiological mechanisms

Abstract: SummaryOenococcus oeni is the dominant species able to cope with a hostile environment of wines, comprising cumulative effects of low pH, high ethanol and SO 2 content, nonoptimal growth temperatures and growth inhibitory compounds. Ethanol tolerance is a crucial feature for the activity of O. oeni cells in wine because ethanol acts as a disordering agent of its cell membrane and negatively affects metabolic activity; it damages the membrane integrity, decreases cell viability and, as other stress conditions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 80 publications
(221 reference statements)
3
10
0
Order By: Relevance
“…In the present study, the phenotype observed by SEM (Figure 2B) demonstrated that ethanol stress resulted in the deformation of T. halophilus cells (HP-ES and ES in Figure 2B). A similar result also reported that ethanol destroyed the cell membrane and affected the industrial performance of O. oeni (Bonomo et al, 2018). In this study, the degree of cell deformation was apparently improved after preadaptation at 45 • C for 1.5 h (Figure 2B, HP-ES), which suggested that heat preadaptation contributed to ethanol resistance by maintaining the morphology of cells at a normal condition.…”
Section: Discussionsupporting
confidence: 84%
“…In the present study, the phenotype observed by SEM (Figure 2B) demonstrated that ethanol stress resulted in the deformation of T. halophilus cells (HP-ES and ES in Figure 2B). A similar result also reported that ethanol destroyed the cell membrane and affected the industrial performance of O. oeni (Bonomo et al, 2018). In this study, the degree of cell deformation was apparently improved after preadaptation at 45 • C for 1.5 h (Figure 2B, HP-ES), which suggested that heat preadaptation contributed to ethanol resistance by maintaining the morphology of cells at a normal condition.…”
Section: Discussionsupporting
confidence: 84%
“…Low pH and ethanol stress appeared to be the crucial factors that decrease the viability of O. oeni in wine, as they both strongly influenced cell growth 4,5 . Ethanol strongly influenced cell membrane fluidity, and low pH inhibited cell malolactic activity 4,6 . Nonetheless, O. oeni has developed a variety of ways to escape or to tolerate wine conditions.…”
Section: Introductionmentioning
confidence: 99%
“…This inhibitory effect of ethanol is in agreement with the model for biofilm formation by Gram-positive bacteria ( Vlamakis et al, 2013 ), where ethanol may exert its inhibitory activity at two levels: (1) acting as a biofilm disruptor ( Böttcher et al, 2013 ) by interacting with the exopolysaccharides produced by planktonic bacteria to form the biofilm, and thus, disrupting the required aggregation for biofilm formation; and (2) as a bactericide molecule, provoking bacterial death, and, consequently, decreasing the density of viable cells, which results in retarding or preventing the formation of biofilm. The mechanisms of ethanol stress in O. oeni , and its molecular response are well known and have been previously reported ( Bonomo et al, 2018 ), whereas to our knowledge, this is the first report describing the response of L. mesenteroides to ethanol.…”
Section: Resultsmentioning
confidence: 61%